Application of Collaborative Mobile System in AR-Based Visualization, Data Storage and Manipulation - Wang, Xiangyu; Truijens, M.; Hou, Lei; Wang, Ying (Springer Berlin Heidelberg, 2013)
Building Information Modeling (BIM) is a technology that can be applied in numerous fields, such as construction management, facility operation and structure and MEP design. BIM enables the representations of digital building information at any construction stages. However, very few instances have been investigated regarding how to apply BIM to effectively facilitate the collaborative work such as planning, design, and information sharing. This paper introduces a collaborative mobile system which integrates a context-aware Augmented Reality (AR) visualization with BIM. The BIM plus AR system visualizes the as-planned data onto the as-built environment. The applications based on this system give the possibility of using this system to address some of the real problems and issues from Australian Liquefied Natural Gas (LNG) construction industry, such as low productivity in retrieving information, tendency of committing error in assembly, low efficiency of communication and problem solving, etc.